Reference Values of Grip Strength Measured with a Jamar Dynamometer in 1526 Adults with Intellectual Disabilities and Compared to Adults without Intellectual Disability - Cuesta-Vargas, Antonio; Hilgenkamp, Thessa I.M. (PLoS One, 2015)
Aim: The aim of this study was to investigate grip strength in a large sample of people with intellectual disabilities, to establish reference values for adults with intellectual disabilities (ID) and compare it to adults without intellectual disability. Methods: This study analysed pooled baseline data from two independent studies for all 1526 adults with ID: Special Olympics Funfitness Spain (n = 801) and the Dutch cross-sectional study 'Healthy aging and intellectual disabilities' (n = 725). Results: The grip strength result of people with ID across gender and age subgroups is presented with CI95% values from higher 25.5-31.0 kg in male younger to lower 4.3-21.6 kg in female older. Conclusion: This study is the first to present grip strength results of a large sample of people with ID from 20-90 years of age. This study provides reference values for people with ID for use in clinical practice.
Keywords: Músculos - Potenciación - Minusválidos; Grip Strength; Dynamometer; Adults with Intellectual Disabilities; Hand Strength